Skyhook - Nance, John J. (New York : G. P. Putnam's Sons, 2003)
Dr. Ben Coles investigates suspicions that his new airplane safety technology has been sabotaged, while pilot's daughter April Rosen tries to figure out what caused her father's near-collision in midair.
National College of Business and Arts
Keywords: Aeronautics -- Safety measures -- Fiction; Suspense fiction